1955
DOI: 10.3181/00379727-89-21917
|View full text |Cite
|
Sign up to set email alerts
|

Renal Blood Flow in Anuric Human Subject Determined by Use of Radioactive Krypton 85

Abstract: when CInulin, CPAH, CUrea, and G r e a t . were +I 0 0 o m O o o W M d o o a o o a ooM*m d C;I* M M t o by guest on July 28, 2015

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
3

Year Published

1962
1962
1992
1992

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 1 publication
(1 reference statement)
0
21
0
3
Order By: Relevance
“…Four mechanisms have been implicated: (a) renal vasoconstriction, (b) development of an aglomerular shunt pathway, (c) tubular obstruction, and (d) back leakage of filtrate. Although observations have been made which could be compatible with the latter three possibilities (1)(2)(3)(4)(5)(6), the majority of recent data support alterations in renal resistance as the major determinant of diminished filtration in acute renal failure (7)(8)(9)(10)(11)(12). Data obtained from micropuncture and hemodynamic studies have led to the view that marked afferent arteriolar constriction decreases effective filtration pressure and glomerular filtration rate.…”
Section: Introductionmentioning
confidence: 81%
“…Four mechanisms have been implicated: (a) renal vasoconstriction, (b) development of an aglomerular shunt pathway, (c) tubular obstruction, and (d) back leakage of filtrate. Although observations have been made which could be compatible with the latter three possibilities (1)(2)(3)(4)(5)(6), the majority of recent data support alterations in renal resistance as the major determinant of diminished filtration in acute renal failure (7)(8)(9)(10)(11)(12). Data obtained from micropuncture and hemodynamic studies have led to the view that marked afferent arteriolar constriction decreases effective filtration pressure and glomerular filtration rate.…”
Section: Introductionmentioning
confidence: 81%
“…Bull, Joekes, and Lowe (24) and Sirota (25), using the direct Fick-PAH technique, concluded that RPF was extremely low during the late oliguric and early diuretic phases of acute tubular necrosis. However, Conn, Wilds, and Helwig (7), Brun and colleagues (15), Munck (16), and Meriel, Galinier, and Suc (26), employing the gas diffusion method to study RBF, demonstrated in both dogs and humans with severe oliguria that RBF was not negligible, but 30 to 50 per cent normal in most studies. These flows are compatible with considerable glomerular filtration.…”
Section: Discussionmentioning
confidence: 99%
“…These flows are compatible with considerable glomerular filtration. Two patients during oliguria had normal blood flow values (15,26). Using krypton85, we have observed a normal RBF in a patient with oliguric acute renal failure after a hemolytic transfusion reaction (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…
The oliguria of acute renal failure has been attributed to tubular obstruction (1-12), "leakage" of the glomerular filtrate through rents in the tubular wall (13)(14)(15)(16)(17)(18)(19), and vascular mechanisms of various types (20)(21)(22)(23)(24)(25). In a previous paper, it was shown that the oliguria of mercury-induced acute renal failure in the rat reflects a primary decrease in glomerular filtration rate and cannot be attributed to tubular mechanisms (26).
…”
mentioning
confidence: 99%